Anatomical Step-by-Step Dissection of Complex Skull Base Approaches for Trainees: Surgical Anatomy of the Frontotemporal and Orbitozygomatic Craniotomies - Carlstrom, Lucas P.; Graffeo, Christopher S.; Leonel, Luciano CPC; Perry, Avital; Link, Michael J.; Peris-Celda, Maria (Journal of Neurological Surgery Part B: Skull Base, 2023)
Introduction Although many neuroanatomic atlases have been published, few have detailed complex cranial approaches and pertinent anatomic considerations in a stepwise fashion intended for rapid comprehension by neurosurgery students, residents, and fellows.Methods Five sides of formalin-fixed latex-injected specimens were dissected under microscopic magnification. The frontotemporal and orbitozygomatic approaches were performed by neurosurgical residents and fellows at different training levels with limited previous experience in anatomical dissection mentored by the senior authors (M.P.C. and M.J.L.). Meticulous surgical anatomic dissections were performed until sufficient visual and technical completion was attained, with parameters of effectively demonstrating key surgical steps for educational training purposes. Following the completion of dissection and three-dimensional photography, illustrative case examples were reviewed to demonstrate the relative benefits and optimal applications of each approach.Results The frontotemporal and orbitozygomatic approaches afford excellent access to anterior and middle skull base pathologies, as well as the exposure of the infratemporal fossa. Key considerations include head positioning, skin incision, scalp retraction, fat pad dissection and facial nerve protection, true or false MacCarty keyhole fashioning, sphenoid wing drilling and anterior clinoidectomy, completion of the craniotomy and accessory orbital osteotomy cuts, dural opening, and intradural neurovascular access.Conclusion The frontotemporal and orbitozygomatic approaches are core craniotomies that offer distinct advantages for complex cranial operations. Learning and internalizing their key steps and nuanced applications in a clinical context is critical for trainees of many levels. The orbitozygomatic craniotomy in particular is a versatile but challenging approach; operative-style laboratory dissection is an essential component of its mastery and one that will be powerfully enhanced by the current work.
Keywords: surgical anatomy; cadaveric dissection; frontotemporal craniotomy; orbitozygomatic craniotomy; surgical approach selection; neurosurgical training